1989
DOI: 10.1152/jappl.1989.66.4.1626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of positive nasal pressure on upper airway pressure-flow relationships

Abstract: To determine the influence of changes in nasal pressure (Pn) on airflow mechanics in the upper airway, we examined the effect of elevations in Pn on upper airway resistance and critical pressure (Pcrit) during stage I/II sleep in six patients with obstructive sleep apnea. When Pn was elevated above a Pcrit, periodic occlusions of the upper airway were eliminated and inspiratory airflow limitation was demonstrated by the finding that inspiratory airflow (VI) became maximal (VImax) and independent of fluctuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
61
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 0 publications
9
61
0
2
Order By: Relevance
“…As current was increased to 2 mA (middle panel) maximal inspiratory airflow (V I max) increased during the stimulated compared with unstimulated breaths. Nevertheless, inspiration remained flow-limited, as evidenced by an early peak in inspiratory airflow followed by a roll-off and plateauing of inspiratory flow later in inspiration (indicative of "negative effort dependence," a recognized phenomenon in collapsible biologic conduits) (25,26). When the stimulus intensity was increased to 2.5 mA, V I max increased further, and inspiratory airflow no longer plateaued, indicating the flow limitation had been abolished.…”
Section: Single Breath Stimulation Airflow Responsesmentioning
confidence: 99%
“…As current was increased to 2 mA (middle panel) maximal inspiratory airflow (V I max) increased during the stimulated compared with unstimulated breaths. Nevertheless, inspiration remained flow-limited, as evidenced by an early peak in inspiratory airflow followed by a roll-off and plateauing of inspiratory flow later in inspiration (indicative of "negative effort dependence," a recognized phenomenon in collapsible biologic conduits) (25,26). When the stimulus intensity was increased to 2.5 mA, V I max increased further, and inspiratory airflow no longer plateaued, indicating the flow limitation had been abolished.…”
Section: Single Breath Stimulation Airflow Responsesmentioning
confidence: 99%
“…The prevalence of snoring is high; 25-50% of middle-aged males are estimated to snore regularly [3,6]. Male sex, obesity, alcohol, sedatives, smoking and nasal obstruction are generally believed to be causative factors in the pathogenesis of snoring [3,[7][8][9][10].…”
mentioning
confidence: 99%
“…Several studies have shown that the mechanical properties of UA in children and adults with OSAS can be predicted by the behaviour of a collapsible tube described as a Starling resistor [21][22][23][24]. Therefore, this model was used to study the response of APAP devices to mechanical behaviour of the UA.…”
mentioning
confidence: 99%